Does Competition from Informal Firms Hurt Job Creation by Formal Firms? Evidence Using Firm-Level Survey Data - Amin, Mohammad (World Bank, Washington, DC, 2021)
The informal sector is an important source of livelihoods and jobs for a vast majority of people in developing countries. However, there is concern that the informal sector may undermine job creation in the formal sector. According to the “parasite” view of informality, informal firms can compete against formal firms, and often "unfairly" so as they do not have to comply with costly regulations and pay taxes. This "unfair" advantage makes it difficult for formal firms to compete against informal firms, implying a significant loss of formal sector jobs. Using firm-level survey data for manufacturing small and medium-size enterprises in 109 mostly developing countries, this study estimates the impact of competition from informal firms on the growth rate of employment among formal sector small and medium-size enterprises. The results show that the growth rate of employment declines significantly as competition from informal firms rises. According to the baseline specification, for each one standard deviation increase in informal competition, the employment growth rate declines by 1 percentage point. Consistent with the parasite view of informality, the negative impact on job growth is much larger when the business environment is less conducive to operating formally versus informally due to factors such high corruption, weak rule of law, more burdensome regulations, and high profit tax rate. Several checks are provided against endogeneity concerns.